Filsafat Pendidikan Islam dalam Mendorong Kemandirian Anak melalui Pendekatan Inquiry-Based Learning di KB Assa’diyah Tuban - ulya ainur rofuah (Universitas Islam Nahdlatul Ulama Jepara, 2025)
This study aims to analyze the implementation of Islamic Educational Philosophy in fostering children's independence through the Inquiry-Based Learning (IBL) approach at KB Assa’diyah Tuban. This approach integrates exploration, investigation, discussion, and application, which not only enhance intellectual development but also possess spiritual and moral dimensions. The findings reveal that Inquiry-Based Learning significantly improves children's independence in critical thinking, decision-making, and learning initiative. The implementation of IBL within the framework of Islamic Educational Philosophy is supported by Al-Ghazali’s perspective, which emphasizes direct experience in acquiring knowledge, and Ibn Khaldun’s view on the importance of independence in education. This research confirms that Inquiry-Based Learning contributes not only to children's cognitive development but also to shaping strong Islamic character from an early age.